2020
DOI: 10.3390/ijerph17103746
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Response of Breast Cancer Cells MDA-MB-231 to Docosahexaenoic Acid: Downregulation of Lipid and Cholesterol Metabolism Genes and Upregulation of Genes of the Pro-Apoptotic ER-Stress Pathway

Abstract: Despite considerable efforts in prevention and therapy, breast cancer remains a major public health concern worldwide. Numerous studies using breast cancer cell lines have shown the antiproliferative and pro-apoptotic effects of docosahexaenoic acid (DHA). Some studies have also demonstrated the inhibitory effect of DHA on the migration and invasion of breast cancer cells, making DHA a potential anti-metastatic agent. Thus, DHA has shown its potential as a chemotherapeutic adjuvant. However, the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 123 publications
(139 reference statements)
2
12
2
Order By: Relevance
“…Our results emphasize that DHA effects are mediated, at least in part, by modulation of gene expression and clearly indicate that it mainly interferes with anabolic lipid metabolism primarily targeting the cholesterol synthesis pathway. The observed impact of DHA treatment on the transcriptome is in line with recently published results in breast cancer cells, where 100 µM DHA strongly downregulated genes involved in the cholesterol biosynthesis pathway, especially after 24 h of treatment [46]. Of note, a strong transcriptional component in the repression of SREBP1 activity was observed, suggesting that the control of nSREBP-1 abundance by DHA is not solely at the post-translational level.…”
Section: Discussionsupporting
confidence: 89%
“…Our results emphasize that DHA effects are mediated, at least in part, by modulation of gene expression and clearly indicate that it mainly interferes with anabolic lipid metabolism primarily targeting the cholesterol synthesis pathway. The observed impact of DHA treatment on the transcriptome is in line with recently published results in breast cancer cells, where 100 µM DHA strongly downregulated genes involved in the cholesterol biosynthesis pathway, especially after 24 h of treatment [46]. Of note, a strong transcriptional component in the repression of SREBP1 activity was observed, suggesting that the control of nSREBP-1 abundance by DHA is not solely at the post-translational level.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanisms of ER-dependent DHA-mediated antiproliferative and proapoptotic in breast cancer cells were confirmed by Chénais et al (2020). The results of their study confirmed that DHA mediates strong ER-stress response in MDA-MB-231, which was confirmed by the upregulation of numerous genes involved in heat shock and ROS stress and ER-stress induced apoptosis [127]. In another study, MDA-MB-231 breast cancer cells supplemented with DHA displayed an increased caspase-1 and gasdermin D activation, enhanced IL-1β secretion.…”
Section: Apoptosis and Cell Cyclementioning
confidence: 87%
“…According to the authors, those effects were dependent on the increased ROS production from the intensified β-oxidation and oxidative phosphorylation in cancerous cells as a result of a metabolic switch caused by n-3 PUFA [126]. The mechanisms of ER-dependent DHA-mediated antiproliferative and proapoptotic in breast cancer cells were confirmed by Chénais et al (2020). The results of their study confirmed that DHA mediates strong ER-stress response in MDA-MB-231, which was confirmed by the upregulation of numerous genes involved in heat shock and ROS stress and ER-stress induced apoptosis [127].…”
Section: Apoptosis and Cell Cyclementioning
confidence: 97%
See 1 more Smart Citation
“…In this process, epithelial cells lose their differentiation characteristics and become mesenchymal cells, acquiring migratory and invasive abilities [ 14 ]. Breast cancer is the most frequently diagnosed cancer in women worldwide, and more than 90% of breast cancer deaths are related to tumor metastasis [ 15 , 16 ]. According to previous research, unlike in most other cancer cells, ER stress can block EMT in breast cancer cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%